Comparative Molecular Mechanisms of Biosynthesis of Naringenin and Related Chalcones in Actinobacteria and Plants: Relevance for the Obtention of Potent Bioactive Metabolites - Juan F. Martín; Paloma Liras (MDPI AG, 2022)
Naringenin and its glycosylated derivative naringin are flavonoids that are synthesized by the phenylpropanoid pathway in plants. We found that naringenin is also formed by the actinobacterium Streptomyces clavuligerus, a well-known microorganism used to industrially produce clavulanic acid. The production of naringenin in S. clavuligerus involves a chalcone synthase that uses p-coumaric as a starter unit and a P450 monoxygenase, encoded by two adjacent genes (ncs-ncyP). The p-coumaric acid starter unit is formed by a tyrosine ammonia lyase encoded by an unlinked, tal, gene. Deletion and complementation studies demonstrate that these three genes are required for biosynthesis of naringenin in S. clavuligerus. Other actinobacteria chalcone synthases use caffeic acid, ferulic acid, sinapic acid or benzoic acid as starter units in the formation of different antibiotics and antitumor agents. The biosynthesis of naringenin is restricted to a few Streptomycess species and the encoding gene cluster is present also in some Saccharotrix and Kitasatospora species. Phylogenetic comparison of S. clavuligerus naringenin chalcone synthase with homologous proteins of other actinobacteria reveal that this protein is closely related to chalcone synthases that use malonyl-CoA as a starter unit for the formation of red-brown pigment. The function of the core enzymes in the pathway, such as the chalcone synthase and the tyrosine ammonia lyase, is conserved in plants and actinobacteria. However, S. clavuligerus use a P450 monooxygenase proposed to complete the cyclization step of the naringenin chalcone, whereas this reaction in plants is performed by a chalcone isomerase. Comparison of the plant and S. clavuligerus chalcone synthases indicates that they have not been transmitted between these organisms by a recent horizontal gene transfer phenomenon. We provide a comprehensive view of the molecular genetics and biochemistry of chalcone synthases and their impact on the development of antibacterial and antitumor compounds. These advances allow new bioactive compounds to be obtained using combinatorial strategies. In addition, processes of heterologous expression and bioconversion for the production of naringenin and naringenin-derived compounds in yeasts are described.